ACADEMIC QUALITY IMPROVEMENT MANAGEMENT AT SMP NEGERI 1 WIRADESA - Susdaryanti Eko Setyowati; Rasiman Rasiman; Sumarno Sumarno (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study aims to describe the management of academic quality improvement at SMP Negeri 1 Wiradesa, Pekalongan Regency. The research employs a qualitative approach with a case study design. The research subjects include the principal, vice principal for curriculum affairs, teachers, administrative staff, school committee members, and parents. Data collection techniques involve interviews, observations, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the management of academic quality improvement includes: (1) planning, through identifying academic quality needs, analyzing problems, formulating goals and targets, and preparing policies and budgets; (2) organizing, through the formation of an academic quality team, clear task distribution, regular coordination, and the involvement of parents and the school committee; (3) implementation, through directing and organizing activities, motivating the team, and monitoring program implementation; and (4) supervision, through structured evaluations, the use of appropriate assessment instruments, and follow-up on evaluation results. The findings of this study are expected to serve as a reference for other schools in developing sustainable strategies for improving academic quality.